Custom-hired tractor services and returns to scale in smallholder agriculture: a production function approach - Takeshima, Hiroyuki (Wiley, 2017)
Historically, agricultural transformation has often accompanied the increase in the returns to scale. Little direct evidence exists, however, on what actually causes such increase, despite the knowledge of many factors that are associated with this increase. We fill this knowledge gap by testing whether hiring in tractor services has raised returns to scale in agriculture at the household level in Nepal Terai that has undergone rapid growth in the tractor use through custom‐hiring services. Using Switching Regression and Inverse‐Probability‐Weighted Generalized Method of Moments, we address two sources of endogeneity involved with the estimation of returns to scale; (1) farmers’ self‐selection on whether to hire in tractor services and (2) use of inputs in the production function. For both Cobb‐Douglas and Translog production function specifications, we find that hiring in tractor services significantly increased the returns to scale in agricultural production by about 0.2 ∼ 0.3 among farm households not owning tractors, for which suitable control groups are found. Findings are robust under various alternative specifications.